IMPROVING STUDENTS’ CRITICAL READING ABILITY: COOPERATIVE LEARNING STRATEGY - Emy Sudarwati; Yana Shanti Manipuspika (Universitas PGRI Yogyakarta, 2021)
This study deals with a strategy named Group Discussion model of CooperativeLearning strategy applied in the teaching of Critical Reading course at English Study Program,Brawijaya University. By using that strategy, it is expected that the problem in CriticalReading class can be solved and students’ ability in critical reading will, in turn, be improved.The design of the study is Classroom Action Research (CAR) since the study is aimed atimproving the students’ critical reading ability and solving the classroom’s problems on theteaching of reading. Based on its characteristics, the classroom action research is donerepeatedly until those problems can be solved. Dealing with the classroom setting, the study isdirected to develop the teaching strategy in order to find out a solution to the classroom’sproblem in the teaching of reading. This study reveals that Cooperative Learning strategy hassuccessfully improved students’ critical reading ability. In doing so, there are stages conductednamely, having cooperative work organization, using appropriate media, having creativity (forteachers), monitoring teaching and learning processes closely, and giving students feedback ontheir work. In conclusion, Cooperative Learning can be beneficial for students’ learning incritical reading as it can make students active and enjoy the classroom activities. However, italso has weaknesses such as time consuming and less appropriate for classes with biggernumber of students. Despite the weaknesses, teachers are still recommended to apply thisstrategy in critical reading classes.